The Correlation Between Mingle Night Activity and Students’ English-Speaking Skill - Abdullah Wahyu Hidayat; Ari Prasetyaningrum; Usuluddin Usuluddin; M. Adib Nazri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
English proficiency is an essential competence, yet students often face psychological barriers such as speaking anxiety. The interactive Mingle Night program is implemented as a solution to facilitate spoken communication through group discussions and presentations. The primary objective of this research was to investigate the statistical correlation and the relationship strength between students' active participation in Mingle Night activities and their objective English speaking skills at Bestone Education. This study employed a quantitative correlational design with a sample of 30 students selected via simple random sampling from a total population of 50 students. Data collection utilized a 20-item Likert scale questionnaire to measure participation levels and a structured oral test rubric to assess speaking components. The collected data were subsequently analyzed using the Pearson Product-Moment Correlation test via SPSS software. The statistical analysis revealed a significance value of 0.408 (p > 0.05) and a correlation coefficient (r) of 0.157. Based on these results, it is concluded that the Null Hypothesis (H0) is accepted, proving there is no statistically significant correlation between Mingle Night participation and students' speaking skills, and the relationship is categorized as very weak. This lack of correlation is primarily attributed to the extremely limited one-week observational timeframe. While one week is sufficient to lower speaking anxiety, it is theoretically and empirically inadequate to produce measurable objective improvements in linguistic components.